Pinoresinol enhances oral barrier integrity and function in human buccal cell monolayers - Soo-Bin Shin; Young-Min Kim; Ha-Young Park (PLoS ONE, 2025)
The oral epithelial barrier plays a crucial role in maintaining oral health by protecting against microbial invasion and mechanical stress while regulating selective permeability. Disruption of this barrier contributes to inflammation and the development of oral diseases such as gingivitis and periodontitis. Pinoresinol, a lignan with antioxidant, antimicrobial, and anti-inflammatory properties, has demonstrated health benefits in systemic diseases; however, its effects on oral epithelial barrier integrity remain unclear. This study investigated the potential of pinoresinol to enhance oral epithelial barrier function using TR146 cell monolayers. Pinoresinol treatment significantly reduced apparent permeability and increased transepithelial electrical resistance, indicating improved barrier integrity. Additionally, pinoresinol upregulated the expression of tight junction-associated molecules, including occludin, MarvelD3, claudin-1, and claudin-3, at both the mRNA and protein levels, enhanced their localization as shown by immunofluorescence. These findings suggest that pinoresinol reinforces the oral epithelial barrier and may help prevent barrier dysfunction associated with oral diseases.